2010
DOI: 10.1186/ar3088
|View full text |Cite
|
Sign up to set email alerts
|

TAM receptor ligands in lupus: Protein S but not Gas6 levels reflect disease activity in systemic lupus erythematosus

Abstract: IntroductionThe TAM (tyro 3, axl, mer) kinases are key regulators of innate immunity and are important in the phagocytosis of apoptotic cells. Gas6 and protein S are ligands for these TAM kinases and bind to phosphatidyl serine residues exposed during apoptosis. In animal models, absence of TAM kinases is associated with lupus-like disease. To test whether human systemic lupus erythematosus (SLE) patients might have deficient levels of TAM ligands, we measured Gas 6 and protein S levels in SLE.Methods107 SLE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 50 publications
4
72
0
1
Order By: Relevance
“…1, C and F and data not shown). The concentration of the free form of PROS1 is ϳ100 nM, which is a hundred times higher than GAS6 concentration that is lower than 0.5 nM in human plasma (46,47). The fact that we did not observe activation of AXL by human plasma or FBS might also be explained by studies reporting that serum GAS6 exists in a complex with naturally occurring sAXL (48).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1, C and F and data not shown). The concentration of the free form of PROS1 is ϳ100 nM, which is a hundred times higher than GAS6 concentration that is lower than 0.5 nM in human plasma (46,47). The fact that we did not observe activation of AXL by human plasma or FBS might also be explained by studies reporting that serum GAS6 exists in a complex with naturally occurring sAXL (48).…”
Section: Discussionmentioning
confidence: 98%
“…Many cancers, including breast cancer, demonstrate elevated GAS6 production along with AXL and MER overexpression (15), whereas lupus patients show different profiles of soluble TAM receptors and free PROS1 and GAS6 in plasma, which are also associated with common genetic variants and stages of disease (45,46). Therefore, one of the important utilities of these TAM reporter cell lines is to assess the activity of functional TAM ligands, as current conventional ELISA technology only provides information on the ligand concentrations, independent of whether the ligand is active or inactive.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our receiver-operating characteristics analysis for identifying patients with active lupus showed that the area under the curve for Gas6 was higher than that of anti-dsDNA antibody, C3, C4 and ESR [77]. Several studies have suggested that the levels of free protein S may be lower in lupus patients; we showed that free protein S levels were decreased in SLE patients with serositis, hematologic, immunologic and neurologic disorders, and correlated with C3 and C4 [76]. A recent study evaluated plasma levels of components of the TAM system in lupus patients, and showed that plasma Gas6 and all 3 soluble receptor levels were higher in lupus, and that free protein S was lower [79].…”
Section: Tam Receptor and Ligandsmentioning
confidence: 57%
“…However, strong correlations with SLEDAI, complement reduction and anti-dsDNA antibody titer were found for only sMer, not for sAxl. An initial study evaluating plasma Gas6 in 107 SLE patients showed that levels were elevated in patients with neurologic or hematologic involvement, but were not correlated with disease activity markers [76]. However, two recent studies showed that Gas6 levels were elevated in lupus patients and correlated with disease activity markers, including SLEDAI, ESR and complement levels [77,78].…”
Section: Tam Receptor and Ligandsmentioning
confidence: 99%
“…Így a veleszületett immunfolyamatok lezajlását a pro-és antiinflammatórikus effektor molekulák egyfajta interreguláló szabályozása együttesen szabja meg. Ezek alapján nem meglepő, hogy a TAM szignalizáció alacsony -vagy éppen túlzott mértékű -GAS6, illetve ProS kifejeződés következtében létrejött helytelen működése súlyos következményekkel járva szisztémás lupus erythematosus (SLE), vagy szeptikus sokk kialakulásához vezethet (Borgel, 2006;Suh, 2010 (Prasad, 2006;Ye, 2011). Azonban az általunk -elsőként -megfigyelt, a mikrobiális ágensek közül a poly I:C kezelés után létrejött TYRO3 és MER génexpresszió csökkenések valószínűsítik, hogy ezek a receptorok a félprofesszionális immunsejtként számon tartott keratinocitákban a veleszületett immunfolyamatokban is szerepet játszanak.…”
unclassified